Innovative Management of Regional Enterprises based on the Integration of Analogue and Digital Models - Alabugin, Anatoly A.; Oreshkina, Natalya S. (Economy of Regions, 2021)
The sustainable development of regional enterprises is negatively affected by uncertainty arising from external factors of the current economic crisis. Due to resultant inconsistencies in their interaction, these entities may experience reduced innovativeness. Therefore, it becomes necessary to derive synergies from the diversified regional resources of industrial enterprises, science and education. The research aims to develop an approach to the high-tech transformation of regional enterprises based on innovative factors of the 5th and 6th technological waves by integrating analogue and digital interactive process models. The proposed method for investigating enterprise interactivity uses quality indicators for regulating the consistency and direction of their functional subsystems. An evaluation of the developed model revealed new possibilities for improving the quality of management in the emerging high-tech intersectoral regional complex (HTIRC) according to a transformation process sustainability criterion. For this purpose, relevant subsystems are defined along with additional change management quality indicators and functions. In order to apply the method, practical recommendations concerning the regulatory structure of the complex are provided. The developed models are useful when making decisions regarding critically unstable organisations. Conditions regulating the transition from the 3rd and 4th to the 5th and 6th technological waves were considered using the corresponding statistical indicators. In order to accelerate this transition process, the amplitude indicators of certain functions and subsystems can be adjusted accordingly. The applied models and methods are effective for analysing and regulating the sustainability of innovative transformations in HTIRC enterprises. Continuing research will focus on developing this method by assessing the coordination of functional effects in terms of the synergy between technologies and organisational methods combining analogue and digital approaches (e.g., vector factor analysis, step- and generalised functions).